THE INFLUENCE OF HUMAN RESOURCE CAPACITY BUDGET IMPLEMENTATION AND MINIMUM SERVICE STANDARDS ON DISASTER PROGRAM QUALITY WITH FINANCIAL MANAGEMENT PERFORMANCE AS A MODERATING VARIABLE - Abdul Hakim; Pambuko Naryoto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of Human Resource Capacity, Budget Implementation, and Minimum Service Standards (SPM) on the Quality of Disaster Program Implementation, with Financial Management Performance as a moderating variable. The research was conducted in the Jabotabek region's BPBDs using a quantitative approach with a census sampling technique, collecting data from 100 respondents via questionnaire. Data analysis employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that Human Resource Capacity, Budget Implementation, SPM, and Financial Management Performance each have a significant positive effect on Program Quality. Furthermore, Financial Management Performance significantly strengthens the positive effects of both Budget Implementation and SPM on Program Quality. These findings confirm that effective disaster management requires not only adequate resources and standards but also robust financial governance to amplify their impact. The study provides strategic implications for strengthening BPBD institutions through an integrated approach to human resources, budgeting, service standards, and financial accountability to enhance community resilience in disaster-prone metropolitan areas.